Characteristics of retinal lesions in patients diagnosed with Ocular Toxoplasmosis who come to a reference center in ophthalmology in Paraguay. - Vera Duarte, Guillermo Raúl; Delgado-Herrera , Claudia Leticia; Castillo Benitez, Verónica Elisa; González Sanabria, Luis; Encina López, Francisco Daniel (Medicina Clínica y Social, 2023)
Introduction: Toxoplasmosis is a parasitic disease, in Latin America the prevalence is relatively high, it is known that the disease is not only the most frequent cause of posterior uveitis, but also the main cause of uveitis itself. In Paraguay there are no published epidemiological data on it. Objective: To determine the characteristics of retinal lesions in patients diagnosed with ocular Toxoplasmosis. Methods: This study is observational, descriptive, cross-sectional, temporally retrospective, with non-probabilistic sampling of consecutive cases. It focused on patients diagnosed with Toxoplasmosis who attended the Ophthalmology service of the Hospital de Clínicas, during the period from June 2020 to February 2022. Results: 54.3% of women were observed, an average of 30.62 +/ - 12.96 years old and 62.8% of urban origin. 88.3% of the cases were unilateral, half were primary episodes, 93.6% acute cases, and 97.9% had an acquired transmission mechanism. Most presented as panuveitis, the most frequent locations of retinochoroidal lesions were the posterior pole (extramacular) and the periphery. The main therapeutic approach was treatment with trimethoprim sulfamethoxazole and systemic corticosteroids, the duration of treatment was 6.51 +/- 1.52 weeks, and the main complications were residual vitritis and ocular hypertension. Discussion: Ocular toxoplasmosis is an important cause of visual morbidity. It is essential to prevent infection by this parasite through hygienic-sanitary measures, as well as early diagnosis and treatment of infected patients, in order to reduce the complications associated with this pathology.
Keywords: Ocular toxoplasmosis; Paraguay; Ophthalmology